Assembly of functionalized carbocycles or N-heterocycles through a domino electrocyclization–[1, 2] migration reaction sequence. Issue 38 (14th October 2015) - Jana, Navendu; Driver, Tom G.
<x xml:space="preserve">Abstract</x> The development of processes that streamline the synthesis of complex, functionalized carbocycles and heterocycles remains a hotly pursued topic because their scaffolds are present in a range of bioactive molecules and electronic materials.